Role of Intermediate Dynamics in Controlling Hydrogenation Selectivity by Heterogeneous Catalysis - Shahrokhi, Masoud (ACS Omega, 2020)
[Image: see text] Selectivity in heterogeneous catalysis is essential while being the most difficult parameters to obtain from theoretical simulations. Although theory holds the key for catalytic design, in the search of complex reaction networks, intermediates are considered static and different configurations for addition reactions are not considered. Here, we present the crucial role of intermediate dynamics to understand reaction selectivity of heterogeneous catalysts by studying the dynamic properties. The hydrogenation of two different intermediates hydroperoxide (OOH) and vinyl (HCCH(2)) is crucial to in the direct synthesis of water peroxide and alkyne semi-hydrogenation are taken as examples on the bare and alloyed surfaces. For them, the reaction network is studied by density functional theory coupled to molecular dynamics to present the role of rotations and how they affect paths for the addition of atomic hydrogen to lead to the products. In summary, the thermodynamic selectivity can be mapped to the dynamic control in the kinetics of the process.